Food insecurity among formerly homeless youth in supportive housing: A social-ecological analysis of a structural intervention. (January 2020) - Brothers, Sarah; Lin, Jess; Schonberg, Jeffrey; Drew, Corey; Auerswald, Colette
Abstract: A growing body of research indicates that structural interventions to provide permanent supportive housing (PSH) to homeless adults within a Housing First approach can improve their health. However, research is lacking regarding the impact of PSH on youth experiencing homelessness. This article seeks to understand how PSH for youth impacts a basic health need—food security— across multiple levels of the social-ecological environment. In January of 2014, San Francisco, California opened the city's first municipally-funded PSH building exclusively designated for transition-aged youth (ages 18–24). We conducted 20 months of participant observation and in-depth interviews with 39 youth from April 2014 to December 2015. Ethnographic fieldnotes and interview transcripts were analyzed using grounded theory. We present our social-ecological assessment regarding food insecurity for formerly homeless youth in supportive housing. We found that although housing removes some major sources of food insecurity from their lives, it adds others. Many of the participating youth were frequently hungry and went without food for entire days. Mechanisms across multiple levels of the social-ecological model contribute to food insecurity. Mechanisms on the structural level include stigma, neighborhood food resources, and monthly hunger cycles. Mechanisms on the institutional level include the transition into housing and housing policies regarding kitchen use and food storage. Interpersonal level mechanisms include food sharing within social networks. Individual level mechanisms include limited cooking skills, equipment, and coping strategies to manage hunger. Although supportive housing provides shelter to youth, effective implementation of the Housing First/PSH model for youth must ensure their access to an affordable nutritious diet. Highlights: Evaluates the multi-level impact of a structural intervention on youth health. Adds youth focus to literature on housing for people experiencing homelessness. Provides evidence that housing for youth should address food insecurity. Argues that youth voice is critical to develop and evaluate youth housing programs. Describes how social-ecological factors contribute to youth food insecurity.